Pengaruh Penundaan Sampel Urin terhadap Hasil Pemeriksaan Kimia pada Pasien Diabetes Melitus - I Kadek Widiantara Putra Dewa (SM Institute, 2025)
DM is a non-communicable disease (NCD) that is classified as a metabolic disorder due to insulin secretion issues. To assess kidney condition in DM mellitus (DM) patients, a supporting examination in the form of urinalysis is used. Urinalysis must be performed immediately once the Urin sample reaches the laboratory. This aims to ensure that the urinalysis can provide accurate results. The purpose of this study is to determine the effect of immediate examination compared to delays of 1 hour and 2 hours on urinalysis results. This research uses an experimental research design. It employs a non-random sampling technique where the samples used are selected based on inclusion and exclusion criteria. The chemical parameters tested include glucose, protein, bilirubin, urobilinogen, erythrocytes, pH, ketones, specific gravity, leukocytes, and nitrites. The examination was carried out using the dipstick method with a total of 50 samples using a urine analyzer. The results of this study found an effect on the protein parameter using the Kruskal Wallis statistical test (p<0.05). Conclusion: There is an effect of the delay in examination on the results of the examination on the protein parameter.